Observation on the Fouling Characteristics of Four Bryozoans in Cochin Harbour - NAIR, N UNNIKRISHNAN (Fishery Technology, 1973)
The occurrence of the: 4 species of bryozoans under study showed that Electra crustulenta PALLAS and Victorella pavida KENT are brackish water forms, Electra bengalensis Stoliczka and Schizoporella Cochinensis Menon and Nair are typical marine forms. It is interesting to note the seasonal succession of these species in Cochin Harbour correspond to the distribution of salinity in this area.